If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8w = -6 + -7w Solving -8w = -6 + -7w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '7w' to each side of the equation. -8w + 7w = -6 + -7w + 7w Combine like terms: -8w + 7w = -1w -1w = -6 + -7w + 7w Combine like terms: -7w + 7w = 0 -1w = -6 + 0 -1w = -6 Divide each side by '-1'. w = 6 Simplifying w = 6
| 5c+6=5c | | 9x^2+6x+2=-6x-2 | | -d-4d=-5d | | 3x^2-12x+35=0 | | -4=-6v+4(v-5) | | -6+8u=8u | | 107-u=214 | | 19=-3y+8(y+8) | | 3x+4=2x+4+x | | 4r+8=3r | | 28=19m+12-11m | | 2-2j=-2j | | 7(1[u-3]1)+3u=19 | | 8(w+3)+7w=-21 | | 2/5(3x+1)=5/2(2x-1) | | 3t=4t-t | | x^2+50x-300=0 | | 3x=2x+31 | | 0=2x^4+x^3+8x-16 | | 3x-6=74-7x | | 400=21m-2 | | x^2+50x+30=0 | | 1/3(5x-1)=7x-2 | | 6w+2w-6w+1=19 | | 3(x+4)/4=5x-1/6 | | 18c+5c-22c-1=7 | | 2x+3/5=5x-1/2 | | 40-7x=12+3x | | x=3.0000 | | 3(2x+10)+5=65 | | 25.5=0.45 | | 4[x+3(x-2)]+1=5 |